PENGARUH LITERASI KEUANGAN TERHADAP SIMPANAN DAN PINJAMAN ANGGOTA KOPERASI DI CITRA AKADEMIKA KUPANG - Yuyanti Selan; Petrus E. de Rozari; Reyner F. Makatita (Universitas Nusa Cendana, 2018)
Cooperative knowledge needs to be owned by Cooperative Members in order to utilize the products ofbank and non-bank financial institutions to be able to manage finances well. Based on the results ofa national surve about Indonesian financial literacy carried out by OJK in 2013, the level offinancial literacy of the Indonesian people was only 21.84% with a level of financial inclusion of59.74%. The majority of financial inclusion in Indonesia is in the banking sector. For Micro, Smalland Medium Enterprises (MSMEs) and cooperatives, the financial literacy level is 15.68% with afinancial inclusion rate of 53.34%. Financial literacy is Knowledge, Understanding, andUtilization in managing finances. This study aims to investigate how much the level of financialliteracy and its effect on savings and loans of members of the Citra Akademika Kupang cooperative.The variables are Knowledge, Understanding, And Utilization that are predicted to have an effecton cooperative member’s Savings and Loan are explained by descriptive analysis and testing usingstatistics. The results showed that the lowest achievement was found in the aspect of Knowledge thathad a negative influence around -32.4% and the highest achievement was found in the Utilizationaspect, which was 74.3% of the members' savings. Utilization affects negatively which ranges from23.7% and it affects significantly to the Loans of cooperative members. This shows that Knowledgeand Understanding are not enough to increase Savings and Loans, meaning that it requires theUtilization of cooperative products to increase Savings and Loans.Keywords: Cooperative Products, Financial Literacy.